PENGARUH EKSTRAK DAUN KELOR TERHADAP PRODUKTIVITAS DAN KUALITAS BAWANG MERAH - Rajiman, Rajiman (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2019)
This research was aimed to study the effected moringa leaf extract to productivity and quality of shallot. The research was implemented at Sendangtirto, Berbah, Sleman for AugustDecember 2018. The research used random block design by 3 replications. The treatment was concentration of moringa leaf extract (K) i.e K0= control (0 %), K1= 2 %, K2= 4 %, K3= 6% dan K4= 8 %. Observation was conducted to plant height 2-5 week after planting, leaves number 2-5 week after planting, bulb number, fresh and dry weight per clumps, fresh and dry weight per cluster, fresh and dry bulb weight per hectare, weight of save bulb, bulb diameter harvest index and total dissolved solids. The data obtained was analysed by variance analysis with 5% level of significance. The results of research showed that increased the increasing concentration of moringa leaf extract didnt affected significantly to productivity and quality of shallot, except affected significantly to leaf number 3 and 5 weeks after planting.